Pemikiran Khalid Abdullah Yahya Blankinship Tentang Terjemahan Bahasa Inggris - Firdausiyah, Umi Wasilatul (HERMENEUTIK : Jurnal Ilmu al-Qur'an dan Tafsir, 2020)
A Study of Khalid Blankinship's Thought on the Rhetoric Features of the al-Quran in English Translations. The scope of this research was related to the rhetoric of al-Quran in English translation. The aim of this study was to examine Khalid Blankinship's thoughts which concern on the English translation of al-Quran problems which in fact English is an international language. In this English translation was found a problem in terms of the rhetorical features of al-Quran. This study used an analytical-descriptive method to explain the problems of the rhetorical features of the English translation of al-Quran which presented on Blankinship's work The Inimitable Qur'an. Meanwhile, the results of this study were related to the findings of Blankinship about problems in the English translation rhetoric, it does not fully provide the true meaning of al-Quran. This is because the rhetoric of al-Quran is different from English and may also caused by the different scientific, social and cultural backgrounds of the translators.